Spiritualitas Fransiskan dalam Perspektif Teologi Perdamaian dan Dialog Antaragama: Studi Historis-Teologis Atas Warisan Santo Fransiskus - Rikha Emyya Gurusinga; Regina Dipa Gurusinga (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
This article examines the Franciscan spirituality of Saint Francis of Assisi through the lens of peace theology and interreligious dialogue. Amid escalating religious and cultural tensions in today’s world, Francis’ spiritual legacy offers a new paradigm that integrates Christian mysticism with universal peacemaking praxis. This study employs a historical-theological approach, exploring Francis’ encounter with Sultan Malik al-Kamil during the Crusades and its theological significance for interfaith relations. The findings reveal that Franciscan spirituality is not only contemplative but also dynamic and open to interreligious engagement. Its spirit of peace, love for all creation, and simplicity of life provide a unique contribution to a world marked by violence, materialism, and religious exclusivism. This study emphasizes the relevance of Francis’ legacy as a source of inspiration for global dialogue and the building of a culture of peace. Practically, it calls both the Church and multicultural societies to rediscover spiritual values rooted in history to strengthen human solidarity